A case of hypercalcemia with double pathology - Ahmed Abdalla; Ghassan Bachuwa; Samer Al Hadidi (Greater Baltimore Medical Center, 2017)
Hypercalcemia has many causes including primary hyperparathyroidism, malignancy, and other rare etiologies. In most of the cases, hypercalcemia is secondary to one etiology. In this case, we are reporting hypercalcemia with two causes. The initial workup showed primary hyperparathyroidism due to parathyroid adenoma. But because all features were not fully explained by primary hyperparathyroidism, further work-up revealed multiple myeloma. This case represents coexistence of two different diseases, which was rarely reported in the literature previously. Usually, the co-diagnosis was made subsequently after failure to correct hypercalcemia. In our case, both diagnoses were established at the same time of the patient's presentation as of high suspicion. Establishing the diagnosis early will aid in the initiation of treatment in a timely fashion.